MK-NMF: A Novel Multiple Kernel-based Non-negative Matrix Factorization Model to Mini Synergistic Drug Combinations in Cell Lines - Li, Tianyi; Han, Huirui; Chen, Jiaqi; Feng, Dehua; Chen, Zhengxin; Wang, Xuefeng; Liu, Xinying; Zhang, Ruijie; Wang, Qibin; Yu, Lei; Li, Xia; Li, Bing; et al. (Current Bioinformatics, 2025)
<span class=
Keywords: Cancer